Biosynthesis of Silver Nanoparticles by Aspergillus Fumigatus Isolated from Spent Wash Mixed Soil and its Antimicrobial Activity - Daithankar Rohini N., Patil Rajshree R., Aher Vrushali S., Joshi PratikP. (International Journal of Innovative Research in Medical Science, 2018)
In nanotechnology, the synthesis of nanoparticles by using the microbes is a boon for advanced research. In this study, silver nanoparticles were synthesized using the fungus Aspergillus fumigatus with an aqueous solution of AgNO3. Synthesized silver nanoparticles (Ag-NPs) were characterized by UV-visible spectrophotometer. Maximum absorbance was observed at 435 nm in a visible region. The reduction of silver ions was due to amino groups of proteins and other functional groups in the cell-free filtrate of fungi. The formation of stable protein capped with the silver nanoparticles because of reduction of silver ion. The Ag-NPs possess potent antimicrobial activity against Bacillus cereus, Bacillus subtilis, Klebsiella pneumoniae and Pseudomonas aeruginosa.